2008
DOI: 10.1021/ja7100278
|View full text |Cite
|
Sign up to set email alerts
|

Zero Thermal Expansion in PbTiO3-Based Perovskites

Abstract: Most materials expand on heating, known as positive thermal expansion. There are some instances most of which have been discovered in the past decade to exhibit a negative thermal expansion (NTE). [1][2][3][4][5][6][7][8][9] The nature of NTE behavior originates from the effect of atomic vibrations, (e.g., the low-energy transverse mode (ice), 2 the coupled rotation of rigid polyhedra (ZrW 2 O 8 , Fe[Co-(CN) 6 ]), 1,4 and active vibration modes of carbon fullerenes and nanotubes), 7 from the effect of magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
140
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(147 citation statements)
references
References 18 publications
7
140
0
Order By: Relevance
“…[1][2][3] The operating temperature of piezoelectric ceramics is generally limited to one-half of the Curie point ͑T C ͒ due to loss of polarization, typically at temperatures lower than 200°C ͓e.g., 150°C for the conventional piezoelectric materials based on the Pb͑Zr 1−x Ti x ͒O 3 ͑PZT͔͒ with a Curie temperature, T C = 386°C. 4 After excellent piezoelectric properties for ͑1 − x͒BiScO 3 -xPbTiO 3 ͑BS-PT͒ near the morphotropic phase boundary ͑MPB͒ ͑x = 0.64͒ were reported ͑piezoelectric coefficient, d 33 = 460 pC/ N, planar coupling coefficient, k p = 0.56, and T C = 450°C͒ recently, 5,6 the discovery of several promising high temperature piezoelectric materials with high performance followed in the general BiMeO 3 -PbTiO 3 system, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] where Me can be a single cation of valency +3 ͑e.g., Sc 3+ and Fe 3+ ͒ or a mixture of cations with an average valence of +3 ͑e.g., Mg 1/2 Ti 1/2 and Ni 2/3 Nb 1/3 ͒. It has been proposed that the Bi substitution plays an unusual role of considerable enhancement of both Curie temperature ͑T C ͒ and tetragonality ͑c / a͒, which results from a strong coupling between Pb/Bi cations and B-site cations of strong ferroelectric activity, such as Ti, Zn, and Fe.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] The operating temperature of piezoelectric ceramics is generally limited to one-half of the Curie point ͑T C ͒ due to loss of polarization, typically at temperatures lower than 200°C ͓e.g., 150°C for the conventional piezoelectric materials based on the Pb͑Zr 1−x Ti x ͒O 3 ͑PZT͔͒ with a Curie temperature, T C = 386°C. 4 After excellent piezoelectric properties for ͑1 − x͒BiScO 3 -xPbTiO 3 ͑BS-PT͒ near the morphotropic phase boundary ͑MPB͒ ͑x = 0.64͒ were reported ͑piezoelectric coefficient, d 33 = 460 pC/ N, planar coupling coefficient, k p = 0.56, and T C = 450°C͒ recently, 5,6 the discovery of several promising high temperature piezoelectric materials with high performance followed in the general BiMeO 3 -PbTiO 3 system, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] where Me can be a single cation of valency +3 ͑e.g., Sc 3+ and Fe 3+ ͒ or a mixture of cations with an average valence of +3 ͑e.g., Mg 1/2 Ti 1/2 and Ni 2/3 Nb 1/3 ͒. It has been proposed that the Bi substitution plays an unusual role of considerable enhancement of both Curie temperature ͑T C ͒ and tetragonality ͑c / a͒, which results from a strong coupling between Pb/Bi cations and B-site cations of strong ferroelectric activity, such as Ti, Zn, and Fe.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, most recent studies have been focusing on nonscandium perovskites. [12][13][14][15][16][17][18][19][20][21][22][23][24] In fact, possible new compositions in BiMeO 3 -PbTiO 3 -based systems are plenty, because B-site Me of BiMeO 3 could be any combination, which gives an average valence of +3. According to the currently available literature, however, the design of BiMeO 3 -PbTiO 3 piezoelectrics faces a significant challenge in that only few systems form a MPB with PbTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the abnormal thermal expansion (ATE) property including zero thermal expansion (ZTE) and negative thermal expansion (NTE) has become an advanced research focus especially in high-precision devices. In recent years, several kinds of materials with ATE property have been discovered, such as LiAlSiO4 (β-eucryptite), ZrW2O8, [3] ScF3, [4,5] PbTio3-based compounds, [6] La(Fe, Si)13-based compounds [7][8][9][10] and some antiperovskite manganese nitrides [2,11] . It is noteworthy that most of ATE materials are tuned to adjust the temperature range of ATE moving towards higher temperature span.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is demonstrated that adding Bi(Zn 1/2 Ti 1/2 )O 3 (BZT) into BF-PT to form ternary solid solution paves the road to obtain both mechanical and insulating robust ceramics for surveying their piezoelectric properties, which takes the following advantages: 1) negative TEC decreases to reduce tensile stresses caused by ferroelectric structural phase transition after sintering; [13][14][15] 2) thermodynamic stability of BiFeO 3 perovskite phase is enhanced to reduce the volatility of Bi 2 O 3 and resulted vacancies in crystallographic lattice; [16][17][18][19] 3) composition range of structural phase boundary is extended widely and 4) ferroelectric T C increased further more than 630 o C. 18,19 In the BF-BZT-PT ternary system, T C was observed around 700 o C for coarse-grained (0.85-y)BF-0.15BZT-yPT solid solution ceramics with 0.30 ≤ y ≤ 0.38 across the tetragonal-tetragonal/rhombohedral coexistent structural phase boundary, which can be modified furthermore through adjusting microstructural grain size and/or element substitution. [18][19][20] In contrast to Bi 4 Ti 3 O 12 system, perovskitestructured BF-BZT-PT ternary system takes advantage of the structural phase boundary like the PZT system intrinsically benefitting for high piezoelectricity 3,21,22 to design high performance ferroelectric piezoceramics suitable for high temperature applications through adjusting composition and crystallographic structure.…”
Section: Introductionmentioning
confidence: 99%